Effect of Saw Palmetto Supplements on Androgen-Sensitive LNCaP Human Prostate Cancer Cell Number and Syrian Hamster Flank Organ Growth - Opoku-Acheampong, Alexander B.; Penugonda, Kavitha; Lindshield, Brian L. (My University, 2017)
Saw palmetto supplements (SPS) are commonly consumed by men with prostate cancer. We investigated whether SPS fatty acids and phytosterols concentrations determine their growth-inhibitory action in androgen-sensitive LNCaP cells and hamster flank organs. High long-chain fatty acids-low phytosterols (HLLP) SPS >= 750 nM with testosterone significantly increased and >= 500 nM with dihydrotestosterone significantly decreased LNCaP cell number. High long-chain fatty acids-high phytosterols (HLHP) SPS >= 500 nM with dihydrotestosterone and high medium-chain fatty acids-low phytosterols (HMLP) SPS >= 750 nM or with androgens significantly decreased LNCaP cell number (n = 3; p < 0.05). Five-to six-week-old, castrated male Syrian hamsters were randomized to control (n = 4), HLLP, HLHP, and HMLP SPS (n = 6) groups. Testosterone or dihydrotestosterone was applied topically daily for 21 days to the right flank organ; the left flank organ was treated with ethanol and served as the control. Thirty minutes later, SPS or ethanol was applied to each flank organ in treatment and control groups, respectively. SPS treatments caused a notable but nonsignificant reduction in the difference between left and right flank organ growth in testosterone-treated SPS groups compared to the control. The same level of inhibition was not seen in dihydrotestosterone-treated SPS groups (p < 0.05). Results may suggest that SPS inhibit 5 alpha-reductase thereby preventing hamster flank organ growth.
Citation: Opoku-Acheampong, A. B., Penugonda, K., & Lindshield, B. L. (2016). Effect of Saw Palmetto Supplements on Androgen-Sensitive LNCaP Human Prostate Cancer Cell Number and Syrian Hamster Flank Organ Growth. Evidence-Based Complementary and Alternative Medicine, 10. doi:10.1155/2016/8135135
Keywords: Serenoa-Repens Permixon(R); Free Fatty-Acids; Beta-Sitosterol; 5-Alpha-Reductase Activity; Topical Application; Rat Prostate